2012
DOI: 10.1021/nl301164v
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Thinning of MoS2: On Demand Generation of a Single-Layer Semiconductor

Abstract: Single-layer MoS(2) is an attractive semiconducting analogue of graphene that combines high mechanical flexibility with a large direct bandgap of 1.8 eV. On the other hand, bulk MoS(2) is an indirect bandgap semiconductor similar to silicon, with a gap of 1.2 eV, and therefore deterministic preparation of single MoS(2) layers is a crucial step toward exploiting the large direct bandgap of monolayer MoS(2) in electronic, optoelectronic, and photovoltaic applications. Although mechanical and chemical exfoliation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

22
517
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(554 citation statements)
references
References 35 publications
22
517
2
Order By: Relevance
“…It is therefore critical to find a simple and efficient method to fabricate monolayer phosphorene. Recently, it has been demonstrated that layer-by-layer thinning of multilayers of MoS2 under plasma or laser irradiation is an efficient approach to get monolayer MoS2 15,16 . Here, we demonstrate plasma thinning also works as an effective way to achieve monolayer phosphorene.…”
Section: Resultsmentioning
confidence: 99%
“…It is therefore critical to find a simple and efficient method to fabricate monolayer phosphorene. Recently, it has been demonstrated that layer-by-layer thinning of multilayers of MoS2 under plasma or laser irradiation is an efficient approach to get monolayer MoS2 15,16 . Here, we demonstrate plasma thinning also works as an effective way to achieve monolayer phosphorene.…”
Section: Resultsmentioning
confidence: 99%
“…This method is not scalable, however, and does not allow systematic control of flake thickness and size. Recently, a focused laser spot has been used to thin MoS 2 down to monolayer thickness by thermal ablation with micrometre-scale resolution, but the requirement for laser raster scanning makes it challenging for scale-up 42 .…”
mentioning
confidence: 99%
“…Such observations, mostly on mechanically exfoliated layers of MoS 2 from single crystals, provided enough impetus to explore innovative methods for large-scale synthesis of atomically thin MoS 2 layers [3,[11][12][13][14][15]. Among these, liquid phase exfoliation [3,11], laser thinning [12], as well as the chemical vapor deposition (CVD) method [13][14][15] are now being utilized to synthesize large-scale area MoS 2 layers.…”
mentioning
confidence: 99%
“…Among these, liquid phase exfoliation [3,11], laser thinning [12], as well as the chemical vapor deposition (CVD) method [13][14][15] are now being utilized to synthesize large-scale area MoS 2 layers. However, the materials produced using these techniques are, in general, susceptible to structural disorder [16,17].…”
mentioning
confidence: 99%